2015
DOI: 10.1371/journal.pone.0123584
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Bacterial and Viral Infections Associated with Adult Asthma Exacerbations in Clinical Practice

Abstract: BackgroundViral infection is one of the risk factors for asthma exacerbation. However, which pathogens are related to asthma exacerbation in adults remains unclear.ObjectiveThe relation between various infections and adult asthma exacerbations was investigated in clinical practice.MethodsThe study subjects included 50 adult inpatients due to asthma exacerbations and 20 stable outpatients for comparison. The pathogens from a nasopharyngeal swab were measured by multiplex PCR analysis.ResultsAsthma exacerbations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 29 publications
(41 reference statements)
2
62
0
4
Order By: Relevance
“…Similar to previous findings [7][8][9], bacteria were detected in the sputum in these cases. In addition, the number of eosinophils in the peripheral blood and sputum was low, and the patients presented with neutrophilia.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Similar to previous findings [7][8][9], bacteria were detected in the sputum in these cases. In addition, the number of eosinophils in the peripheral blood and sputum was low, and the patients presented with neutrophilia.…”
Section: Discussionsupporting
confidence: 92%
“…Bacteria detected in these cases and in previous reports [7][8][9] enhance mucus secretion [15], inhibit the ciliary beat frequency, and cause airway epithelial injury, thereby impairing mucociliary clearance [16]. Infection with these bacteria also stimulates the cells in the airways and the lung parenchyma to induce pro-inflammatory substrates such as interleukin (IL)-8 and leukotriene B4 [17].…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…In atopic Turkish children with asthma and allergic rhinitis, significantly higher herpes simplex type 1 (HSV-1) IgG seropositivity was detected in the serum than in the matched nonatopic group (13), suggesting a possible relationship between pediatric allergic airway diseases and HSV-1 infections. In adults, higher incidences of HRV-A/B/C, HRSV-A, and metapneumovirus infections were observed in nasopharyngeal swabs during asthma exacerbations (14).…”
Section: The Prevalence Of Viruses In the Airwaysmentioning
confidence: 94%
“…It is evident that bacterial organisms act as important contributors to asthma exacerbations. A study of the bacterial composition of the nasopharynx in adult asthmatic patients indicated that Streptococcus pneumoniae infection was also associated with asthma exacerbations in clinical practice (14). In CRS, inflammation development takes place in the middle meatus.…”
Section: The Prevalence Of Bacteria In the Airwaysmentioning
confidence: 99%